ARTSTEP VIRTUAL EXHIBITION: SOLUSI KREATIF UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN PANCASILA - Munir, Zahra Alfirdausy; MS Khabibur Rahman; Universitas Veteran Bangun Nusantara Sukoharjo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The development of digital technology offers new opportunities to improve the quality of learning in elementary schools, so teachers must be able to utilize technology to support learning activities. There are several technology-based media that teachers can use, one of which is the ArtStep Virtual Exhibition. This study aims to find out the effectiveness of the ArtStep Virtual Exhibition digital media in improving students' motivation and academic achievement in the Pancasila Education subject. The research methodology used is Classroom Action Research (CAR), which consists of two cycles. The analysis results showed a significant increase from cycle 1 to cycle 2. In cycle 1, the average student score was 58.57, most of whom were in the